Diseño y construcción de un graficador de curvas I-V para paneles fotovoltaicos. - Collaguazo Valle, Luis Bryan (2024)
This paper presented the design and construction of a plotter for I-V curves, based on the capacitive load method. This method was applied to acquire the currentvoltage values of photovoltaic systems or modules, with the purpose of analyzing their performance. The manipulation of the plotter was carried out by a small computer known as Raspberry Pi, which makes it possible to evaluate the state of the photovoltaic panels. This evaluation provides accurate information about possible deficiencies or decays that may be affecting the performance of the installation. In general, the present work was carried out in four phases, which are the study, design, construction and evaluation phase. Therefore, initially, the study of the information on the existing methods for the construction of the plotter was made and the most appropriate method was chosen which was the capacitive load, once having clear the method to use we proceeded with the design of the circuit with the help of the software called Proteus and in turn to select the appropriate materials for the construction of the plotter, which consists of voltage and current sensors, power supplies and the raspberry to control all the equipment and display of the graphs on a screen that is connected to it. In addition, it allowed us to store these graphical representations for later análisis. To conclude, experimental tests were carried out on the solar panels located at the Faculty of Energy of the National University of Loja. With these tests it was posible to evaluate the condition of these panels and to confirm the effectiveness of the I-V curve plotter that has been developed. Keywords: I-V curves, I-V curve plotter, capacitive load, Raspberry Pi, photovoltaic systems, Proteus.